SYSTEM ENGINEERING SUPPORT - Provided by Federal Information & News Dispatch, Inc. (FIND) 202-544- 4800 (Commerce business daily, 2001)
NOTICE TEXT: The Centers for Medicare and Medicaid Services (CMS), formerly the Health Care Financing Administration intends to award on a sole source basis, under the Simplified Acquisition Procedure (Dollar Threshold of $100,000) a firm fixed price award to Sage Technologies, 721 Waters Edge Court, Sykesville, MD 21784. CMS requires contractor support to assist in the research of commercial off the shelf (COTS) front-end access tools and in the development of ad hoc methodologies that utilize these tools against CMS data. Effective front-end analysis requires properly designed data models, tuned for the idiosyncrasies of the COTS product as well as CMS? data. CMS requires contractor support in the analysis of the Health Care Information System (HCIS) data models, and in the development of data models for other subject areas in CMS (MADS, APS, Enrollment, etc.) The existing HCIS application allows its users a view of highly summarized Medicare claims data, offering predetermined views of the data. CMS would like to increase data access for its user base and provide ad hoc querying capabilities against expanded data models, allowing the user to create his or her own view of the data. The contractor shall have experience designing front-end applications with emphasis on the ability to design an application that is powerful but user- friendly for CMS staff as well as fiscal intermediaries and carriers. This skill is critical as the CMS user community demands that development staff address usability issues across various skill levels. Experience with the HCIS application design/development process is mandatory. The same user issues/ requirements shall pertain to design models for other data marts developed at CMS. The contractor must have experience with relational design and dimensional modeling. The contractor shall have extensive working knowledge of the HCIS application and familiarity with other Medicare reporting and decision support systems (i.e. APS, Cost Reports, etc). The contractor shall have a comprehensive, detailed understanding of the data requirements that go into building the system as well as the user requirements for the front-end application that makes the data available. The contractor shall have extensive knowledge of the NCH data elements as utilized by the HCIS application and familiarity with the NCH data elements utilized by other Medicare reporting and decision support systems. The contractor shall have an in-depth understanding of the edits and transformations applied in the HCIS summary data programs as well as an understanding of the edits and transformations applied in other Medicare reporting and decision support systems. This information is essential for tuning the COTS products for optimal query and retrieval against CMS data. The contractor shall have experience in modeling Medicare data. The contractor shall have experience designing software for Medicare applications. This experience is essential to assess maintenance and scalability issues. Familiarity with the CMS infrastructure is required, including the mainframe and mid-tier architecture. Familiarity with the National Medicare Utilization Database (NMUD) project, particularly the staging area, is mandatory -- (logical and physical data models, architecture, platform, size and scope of the system). All developers and designers of relational data structures supporting CMS sponsored applications are required to be aware of and adhere to CMS? Data Management standards and procedures. Developers are responsible for producing a logical model and metadata in ERwin in accordance with CMS object naming and design standards, with review and approval by a Central Data Administration representative. All metadata will be imported into Platinum PR/MVS where standardized physical data definitions will be generated.